Pattern of Morbidities in Under Five Children and Health Seeking Behaviour of their Parents - Anne, Rownok Azad; Akhter, Neelima; Shapla, Nahid Reaz; Jesmin, Eva; Begum, Nazma (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: All children, no matter where they born, deserve a healthy start in life. But harsh reality is that, in year 2012, 6.6 million children died in Bangladesh before their fifth birthday. The children constitute a large proportion of the total population of Bangladesh. They are 15 million, the vulnerable or special risk group; deserve exceptional health care as the child mortality and morbidity risks are much higher than their later life. Child morbidity is determined by several complex and inter-related factors in Bangladesh, specially in rural area. Objectives: The objective of this study was to find out the pattern of morbidity of under five children, health seeking behaviour of their parents and the socio-demographic factors affecting those under five children's morbidity. Materials and Methods: This descriptive type of cross sectional study was carried out at Madhupur Thana under a rural area of Tangail District during January 2012 to June 2012 to find out the pattern of morbidities of under five children and health seeking behaviour of their parents. Total 170 mothers were selected purposively to carry out this study. Results: Among the cases of morbidities, 611(100%) sufferings of under five children were recorded from 170 respondents. The highest frequency (133, 21.76%) of sufferings of under five children were from cold, almost the similar number (132, 21.6%) of sufferings were from fever and 116(16.69%) sufferings were from diarrhoea. In this study, health care seeking behaviour for their children were found towards blessings from religious person (Jarphuk/Tabiz-11.77%), spiritual healer (Kobiraj-8.82%), herbal(7.06%), village doctor(20%) drug seller (17.06%), homeopath (12.94%), paramedic (4.71%), MBBS doctors (9.41%) and 8.23% did not take any treatment. Monthly income level of 51.8% respondents were from Taka 5000/- to Taka 10,000/-. On the other hand, only 07 respondents had highest level income of Taka 20,000/- to Taka 30,000/-. The mean income of the mother of under five children was Tk 10,064/- (SD= ± 5709.06). This study revealed that 14 respondents out of 170 did not take any treatment for their under five children. Out of these 14 respondents, 02(14.28%) even did not know the existence of treatment for the morbidity of their under five children. Again, 05(35.71%) respondents had the belief that their children would get cured without any medicine, 04 (28.57%) respondents had no health care centre nearby and 03(21.42%) respondents were unable to bear the treatment cost. Conclusion: Education and awareness of the parents about child health care are important components to reconsider for developing new strategy for improving existing situation of health seeking behaviour of parents for their under-5 children. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 59-63